2021
DOI: 10.1111/1750-3841.15792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infrared ray roasting on oxidation stability and flavor of virgin rapeseed oils

Abstract: Effects of infrared ray roasting (IRR) on the oxidation stability and flavors of virgin rapeseed oil (VROs) at 110−170°C were investigated and compared with traditional roller roasting (TRR). Results showed that IRR samples showed lower acid and peroxides values, higher oxidation stability index, and 2,2‐diphenyl‐1‐picrylhydrazyl radical scavenging activity than TRR ones. IRR samples displayed better thermal expansion of rapeseed for internal fragmentation from microstructures, which facilitated the release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(58 reference statements)
1
11
0
Order By: Relevance
“… Zhou et al (2019) reported that the hexanal, heptanal, (E)-2-hexenal, benzaldehyde, and (E,E)-2,4-decadienal were identified as key volatile compounds in commercial FROs. These products have also been observed in the work of Yu, Wang, Zhang, Liu, and Li (2021) . The majority of aldehydes reported in rapeseed oil have to do with the fatty flavor, but some lead to green, nutty, or rancid odors as well ( Zhang et al, 2021 ).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“… Zhou et al (2019) reported that the hexanal, heptanal, (E)-2-hexenal, benzaldehyde, and (E,E)-2,4-decadienal were identified as key volatile compounds in commercial FROs. These products have also been observed in the work of Yu, Wang, Zhang, Liu, and Li (2021) . The majority of aldehydes reported in rapeseed oil have to do with the fatty flavor, but some lead to green, nutty, or rancid odors as well ( Zhang et al, 2021 ).…”
Section: Introductionsupporting
confidence: 68%
“…FRO is mainly processed by cleaning, roasting, physical pressing, and centrifugation or filtration ( Yu, Wang, Zhang, Liu, & Li, 2021 ). Among these steps, the complex reactions that occur during roasting are essential for creating flavor compounds in FROs during processing ( Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on an investigation of local oil industries, the optimum roasting temperatures of TRR are within 150–170 °C (Yu et al ., 2021). In the pre‐experiment, VROs were determined to better flavour profile at 150–170 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, temperatures of TRR were set from 150 to 170°. The samples were heated using a traditional roller roasting machine (Jiangsu Maisi Machinery Equipment Co., Ltd., Wuxi, Jiangsu) at 150–170 °C for 20 min (Yu et al ., 2021). A handheld digital temperature probe was used to measure temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation